2016
DOI: 10.1002/glia.23043
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-targeted production of interleukin-6 reduces astroglial and microglial activation in the cuprizone demyelination model: Implications for myelin clearance and oligodendrocyte maturation

Abstract: Multiple sclerosis (MS) is a chronic demyelinating disease of the central nervous system. Interleukin (IL)-6 is a pleiotropic cytokine with a potential role in MS. Here we used transgenic mice with astrocyte-targeted production of IL-6 (GFAP-IL6Tg) to study the effect of IL-6 in the cuprizone-induced demyelination paradigm, which is an experimental model of de- and re-myelination, both hallmarks of MS. Our results demonstrated that cuprizone-treated GFAP-IL6Tg mice showed a significant reduction in astroglial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 63 publications
3
37
0
Order By: Relevance
“…In the cuprizone demyelination model, Il-6 induced by short-term cuprizone exposure was primarily located to GFAP 1 astrocytes (Tezuka et al, 2013). Using the GFAP-IL-6 transgenic mice, a recent study reported that chronic IL-6 production by astrocytes induced persistently higher levels of chemokines (CXCL10 and CXCL1) under normal conditions but subdued astroglial and microglial activation after 3 weeks of cuprizone intoxication (Petković, Campbell, Gonzalez, & Castellano, 2016). Consistent with blunted Il-1b and Il-6 production in CYM5442-treated mice during the early phase of cuprizone intoxication, CYM5442 also prevented the upregulation of chemokine Cxcl10 (Figure 5c), a key microglial chemoattractant that is primarily produced by reactive astrocytes as ablation of Cxcl10 gene significantly prevented early microglial activation .…”
Section: Discussionmentioning
confidence: 99%
“…In the cuprizone demyelination model, Il-6 induced by short-term cuprizone exposure was primarily located to GFAP 1 astrocytes (Tezuka et al, 2013). Using the GFAP-IL-6 transgenic mice, a recent study reported that chronic IL-6 production by astrocytes induced persistently higher levels of chemokines (CXCL10 and CXCL1) under normal conditions but subdued astroglial and microglial activation after 3 weeks of cuprizone intoxication (Petković, Campbell, Gonzalez, & Castellano, 2016). Consistent with blunted Il-1b and Il-6 production in CYM5442-treated mice during the early phase of cuprizone intoxication, CYM5442 also prevented the upregulation of chemokine Cxcl10 (Figure 5c), a key microglial chemoattractant that is primarily produced by reactive astrocytes as ablation of Cxcl10 gene significantly prevented early microglial activation .…”
Section: Discussionmentioning
confidence: 99%
“…Proper regulation and control of the inflammatory response is required to protect OLs from damage and to promote remyelination (Diemel, Copelman, & Cuzner, 1998;Marriott et al, 2008;Merson, Binder, & Kilpatrick, 2010;Petković, Campbell, Gonzalez, & Castellano, 2016). In demyelinating diseases such as MS, alterations in the innate immune system contribute to myelin damage, axonal loss and limit remyelination (Podbielska, Banik, Kurowska, & Hogan, 2013).…”
mentioning
confidence: 99%
“…TNF-α and IL-1β) and ROS in microglial cells 40 . Transgenic mice with astrocyte-targeted production of IL-6 showed inefficient removal of demyelinating stimulus-induced degraded myelin and axonal protection in the CC compared to wild type mice 41 , suggesting that IL-6 may impair myelin maintenance and induce axonal injury. In children infected with M.pneumoniae, toll-like receptor (TRL)2 and TRL4, which are expressed in the CC 42,43 , were increased 44 .…”
Section: Enterococcus Faecalis 35mentioning
confidence: 98%